Role of Optical Coherence Tomography in Chorioretinitis - Fayzieva D.B (Genius Journals, 2023)
Chorioretinitis is considered one of the urgent problems among eye diseases, and it is characterized by complications of conservative treatment due to the fact that it occurs mainly among the young, able-bodied population, it has the characteristic of recurrence during the course of the disease, the occurrence of complications, and the presence of an allergic condition to drugs in most patients. The importance of using the optical coherence tomography method in the diagnosis and monitoring of chorioretinitis was studied. Patients with chorioretinitis of different etiology were divided into groups according to gender, age and origin. Patients were monitored by general and special ophthalmological examinations. Optical coherence tomography makes it possible to determine the perifocal inflammatory reaction in focal chorioretinitis of various etiologies, to determine the inflammatory process against the background of disease reactivation and medical treatment, to give qualitative and quantitative characteristics, and to assess the dynamics of the inflammatory process.
Keywords: pathology of the retinal layer; diagnostics